Compliance cost estimates: Survey non-response and temporal framing effects - Sebastian Eichfelder (Arbeitskreis Quantitative Steuerlehre (arqus), 2013)
Due to empirical research, tax and accounting compliance costs are a considerable burden for private businesses. However, cost estimates may be biased due to survey nonresponse and questionnaire framing effects. This paper investigates the impact of both aspects on the estimated cost burden. I do not find significant evidence for a non-response bias. By contrast, my results indicate that framing effects regarding the temporal dimension of cost measurement (temporal framing effects) might alter cost estimates by up to 68 percent downwards (respectively 211 percent upwards). There is also evidence that temporal framing effects are more relevant for small self-employed businesses with limited information capacities and accounting obligations as well as for internal cost burdens.
Keywords: H25; K34; M41; M42; M48; 330; compliance cost measurement; measurement error; non-response bias; temporal framing effect